2021
DOI: 10.1002/pros.24188
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning algorithms can more efficiently predict biochemical recurrence after robot‐assisted radical prostatectomy

Abstract: Objectives: To develop a model for predicting biochemical recurrence (BCR) in patients with long follow-up periods using clinical parameters and the machine learning (ML) methods.Materials Method: Patients who underwent robot-assisted radical prostatectomy between January 2014 and December 2019 were retrospectively reviewed. Patients who did not have BCR were assigned to Group 1, while those diagnosed with BCR were assigned to Group 2. The patient's demographic data, preoperative and postoperative parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Another study on BCR showed that GS detected in the specimen and the pathological stage was closely related to BCR (25). Similarly, Tağcı et al reported a relationship between LNI and early BCR (26) another study by Ekşi et al, risk classification, mpMRI findings, PSM, SVI, and T stage were noted as significant parameters predicting BCR (11). In our study, the multivariate analysis revealed PSA, risk classification, specimen GS, PSM, SVI, and T stage to be the predictive parameters of BCR.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Another study on BCR showed that GS detected in the specimen and the pathological stage was closely related to BCR (25). Similarly, Tağcı et al reported a relationship between LNI and early BCR (26) another study by Ekşi et al, risk classification, mpMRI findings, PSM, SVI, and T stage were noted as significant parameters predicting BCR (11). In our study, the multivariate analysis revealed PSA, risk classification, specimen GS, PSM, SVI, and T stage to be the predictive parameters of BCR.…”
Section: Discussionmentioning
confidence: 88%
“…In our study, the multivariate analysis revealed PSA, risk classification, specimen GS, PSM, SVI, and T stage to be the predictive parameters of BCR. In addition to the nomograms established for this purpose, more advanced algorithms can be created by integrating artificial intelligence and machine learning methods into hospital information systems (5,11). We consider that as the external validation of such created models is undertaken and current knowledge increases, there will be more common and widely accepted models that can predict BCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developments in computer technology have improved analytical methods for handling large-scale data, and machine learning has attracted attention also in the medical eld. Machine-learning techniques are commonly used for data-driven diagnostic and prognostic predictions (9,10) . The greatest advantage of using machine learning is that it can be used to account for the combined, nonlinear effects of numerous variables and can make precise individualized predictions for heterogeneous patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…Developments in computer technology have improved analytical methods for handling large-scale data, and machine learning has attracted attention also in the medical field. Machine-learning techniques are commonly used for data-driven diagnostic and prognostic predictions 9 , 10 . The greatest advantage of using machine learning is that it can be used to account for the combined, nonlinear effects of numerous variables and can make precise individualized predictions for heterogeneous patient populations.…”
Section: Introductionmentioning
confidence: 99%